Introduction. Issue 1 (February 2016) - Bailey, Tom
Abstract : This editor's preface introduces a special issue of Critical Horizons on the theme of "contestatory cosmopolitanism." After identifying the broad failings of the standard cosmopolitan appeal to global community, it presents the defining features of the "contestatory" alternative and introduces the papers in light of them.